Upper and Lower Bounds for Essential Norm of Weighted Composition Operators from Bergman Spaces with Békollé Weights. (29th December 2020) - Subhadarsini, Elina; Sharma, Ajay K.
Abstract : Let σ be a weight function such that σ / 1 − z 2 α is in the class B p 0 α of Békollé weights, μ a normal weight function, ψ a holomorphic map on D, and φ a holomorphic self-map on D . In this paper, we give upper and lower bounds for essential norm of weighted composition operator W ψ, φ acting from weighted Bergman spaces A p σ to Bloch-type spaces B μ .